Synergistic effect of GF9 and streptomycin on relieving gram-negative bacteria-induced sepsis - Wei, Bing; Ma, Yingmin (Frontiers in Bioengineering and Biotechnology, 2022)
Triggering receptor expressed on myeloid cells-1 (TREM-1) regulates inflammation and promotes a vigorous immune response. GF9 is one of the peptides that inhibit the mTREM-1 signaling pathway, thus reducing the inflammatory mediators in diseases including sepsis. Nanotechnology could offer a new complementary strategy for diseases. Streptomycin is also one treatment of sepsis. However, the role of nanoparticles delivered GF9 combined with streptomycin on sepsis had never been discovered. In the present study, cecal ligation and puncture (CLP) and lipopolysaccharide (LPS, Escherichia coli (E. coli) O111:B4) sepsis models were constructed. SDS-PAGE was used to evaluate the size of nano drugs; Western blot was used to detect the protein levels of MMP2 and TREM-1 in cells. The levels of TNF-α and IL-6 were detected by ELISA. Histopathological changes were observed by HE staining. And the nanomedicines of GF9-HFn/Str were successfully constructed. The size of GF9-HFn/Str is 36 kD. The ferritin-based nanoparticle plays a vital role in delivering streptomycin into cells and tissues. GF9 (1.6 μM) and streptomycin (40 μM) co-delivery nanomedicine showed a better effect on promoting overall survival, decreasing E. coli, significantly suppressed the expression levels of inflammatory factors (TNF-α and IL-6), and can reduce lung injury. Our study demonstrated that combination delivery of nanomedicine GF9 and streptomycin have a better effect on overall survival rate, anti-inflammatory, and anti-bacterial in sepsis. Our present study revealed a new potential therapeutic method for sepsis.